Assessment of Harm Reduction Programs in Behavioral Health Clinics (Triangle) for Covered Veterans - M. Ghiasi; M. Farahbakhsh; A. Hekmatpour (طب جانباز, 2013)
Introduction: Studies show that veterans exposed to high-risk behavior and drug use are not offset the effects on different aspects of their health and their families, harm reduction programs carried out in health clinics Behavioural (triangle) can maintain and improve health indicators and quality of life of these people. The aim of this study was to assess the impact of harm reduction programs in behavioral health clinics (triangle) on the health and quality of life of veterans.